Biochemical evaluation of kidney disease - Treacy, Oliver; Brown, Nigel N.; Dimeski, Goce (Translational Andrology and Urology, 2018)
Different biochemical markers exist in both blood and urine for assessing renal function. Most of these biomarkers have advantages and limitations associated with their use, which is important to consider when ordering and utilising them in the clinical setting. The ideal marker should be able to detect acute kidney injury (AKI) at the onset and be used for the diagnosis and ongoing monitoring and management of kidney disease. The search for such a marker is ongoing, as all potential candidates thus far are associated with certain limitations. This article will attempt to compare and contrast established and emerging kidney disease markers.